2003
DOI: 10.1007/bf02914494
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of gastric antisecretory therapy in hospital practice

Abstract: There appears to be a widespread and inappropriate use of PPIs in hospital practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
4
12
1
Order By: Relevance
“…The rate of guideline compliance among non-academic hospitalists was significantly lower than that of academic hospitalists in this study (29% and 50%, respectively). Both rates were within the range reported by other groups, namely 19% to 78% (8,10,11,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). GIP in low risk patients has also been identified in other studies as the major reason for non-compliance (38), in addition to relief of nonspecific abdominal symptoms (33,35,39) or indeterminate chest pain (35), prevention of medication-associated complications (36) and mild forms of gastroesophageal reflux (30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The rate of guideline compliance among non-academic hospitalists was significantly lower than that of academic hospitalists in this study (29% and 50%, respectively). Both rates were within the range reported by other groups, namely 19% to 78% (8,10,11,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). GIP in low risk patients has also been identified in other studies as the major reason for non-compliance (38), in addition to relief of nonspecific abdominal symptoms (33,35,39) or indeterminate chest pain (35), prevention of medication-associated complications (36) and mild forms of gastroesophageal reflux (30).…”
Section: Discussionsupporting
confidence: 82%
“…Four other studies have attempted to identify independent risk factors for non-compliance (28,32,34,38), only two of which adjusted for possible confounding variables through multivariate logistic regression and found good functional status, a prescription initiated by a general practitioner, and a history of an endoscopy evaluation (38) as independent predictors of compliance with the PPI prescription guidelines. Age and gender, similar to our results, were not significant independent predictors (28).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been described in previous studies and in different countries (USA, Sweden, UK) showing that a PPIs considerably excessive usage does exist in inpatient settings, 6,7 that the frequency of PPIs discontinuation is low in long-term users, 8 that there are more difficulties in discontinuing PPIs in GERD than in non-GERD patients 8 and that an educational intervention employed to reduce PPIs inappropriate prescription in the community had no effect on the proportion of patients taking these drugs at the time of hospital admission. 9 In addition, the list of Haroon et al provides another important and exact result: of note, to the majority of medical inpatients PPIs were prescribed with an inappropriate or a poor indication, being lower than expected the number of patients who had endoscopy before starting PPIs therapy.…”
Section: Overutilization Of Proton Pump Inhibitors Therapy In Hospitasupporting
confidence: 91%
“…Naunton et al [8] published a paper which reported that 63% of patients receiving a PPI did not fulfil the Australian Schedule of Pharmaceutical Benefits criteria. An Irish study conducted by Sebastian et al [9] had an identical finding whereby an appropriate indication for PPI therapy was not apparent in 63% of cases. Work carried out by Van Vliet et al [10] in the Netherlands stated that 40% of patients on PPI therapy did not have a registered indication for use.…”
Section: Discussionmentioning
confidence: 84%